RESTRUCTURING OF INDUSTRIAL ENTERPRISE - L. I. Podderegina (Наука и техника)
The paper presents main principles for execution of current and strategic restructuring of national enterprises while using experience of countries with developed market economy. The principles contribute to higher efficiency in internal industrial relations at national industrial enterprises.